Production and Marketing of Agriculture Production in Karnataka - Tammanagouda. S. Goudar, Dr. Nayanatara S. Nayak (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
Agriculture plays a vital role in India’s economy. Around 54.6% of the total workforce is engaged in agriculture and allied sector activities (Census 2011). 42.4% (139.3 million hectares) of the geographical area is reported as net sown area in the country (Agriculture Annual Report, 2021-22). Indian agriculture has been called a “gambling with monsoons” It has always been a risky business and it is subject to changes in the weather. The concept of crop insurance emerges from the fact that agriculture is subject to uncertainties linked to weather conditions and risks of crop loss due to various reasons including extreme weather variations. Crop failure due to adverse climate and lack of rainfall imposes a heavy burden on the farmers, society, and governments, as they must compensate farmers for the loss to sustain agriculture in the long run.